Filsafat Pendidikan Pancasila: Membangun Karakter Unggul di Sekolah Dasar - Sabil, Muhammad Arqam; Shafira, Syifa; Hidayat, Sholeh (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
The researcher's research aims to understand an educational philosophy based on Pancasila in forming good character in elementary schools. The philosophical foundation in the field of education has a very crucial role. Educational philosophy is not only a guide for individuals or educators in thinking deeply about the nature of education, but also reflects the existence of a nation. The quality of education is reflected in the strength and sustainability of the philosophical foundation adopted. Education that is considered good is education that is capable of producing people with character. In the Indonesian context, Pancasila is the foundation of the country's philosophy which is a reflection of the nation's soul. Pancasila is not just an ideology, but also a spirit in working in various fields, especially in the field of education. The practice of Pancasila in education is not just a formality, but includes the overall understanding and integrity of the five principles contained in Pancasila. This is in accordance with the formulation in the preamble to the 1945 Constitution, which includes belief in the Almighty God, just and civilized humanity, Indonesian unity, democracy led by wisdom in deliberation/representation, and social justice for all Indonesian people. The research method used is literature study by referring to related studies and research, as well as applying descriptive-analytical methods in presenting research results. With the hope that in the future, it is hoped that Pancasila can become the main source of reference in building good character in elementary schools.